Real Time Wireless Smart Electrical Energy Meter System - MofeedTurky Rashid (Engineering and Technology Journal, 2014)
Real time smart electrical energy meter network is one of the backbones for modern smart grid. It is very critical to have the right technologies for the efficient operation of smart meter network. In this paper, real time wireless smart electrical energy meter system has been designed and implemented which PIC microcontroller is used for real time energy measurements. In this system, all real time energy measurements will be send to base station through ZigBee wireless sensor network (WSN) for managements and monitoring. Also database will be design to record and manage all data and information of consumers.